Nilai Dasar Collaborative Governance Dalam Studi Kebijakan Publik - Nasrulhaq Nasrulhaq (Kolaborasi : Jurnal Administrasi Publik, 2020)
This paper examines the basic values of collaborative governance based on theoretical studies and empirical facts in an integrative manner. The starting point study of the relationship between stakeholders in each stage of public policy is increasingly complex. Based on this complexity, studies on governance also experience dynamics. The collaborative framework in governance provides a meaning that is more than just governance. Collaborative governance is a concept in public policy that has developed in the last few decades. In principle, the collaborative is different from the network as well as the partnership. There is an essential value attached to it. Henceforth, it becomes part of its characteristics. The basic values referred to are consensus orientation, collective leadership, multidirectional communication, and resource sharing. The four basic values are integrated into one integrated process in any collaborative governance action.